Enhanced transformation by a simian virus 40 recombinant virus containing a Harvey murine sarcoma virus long terminal repeat. - Kriegler, M (1983)
We have constructed a recombinant simian virus 40 (SV40) DNA containing a copy of the Harvey murine sarcoma virus long terminal repeat (LTR). This recombinant viral DNA was converted into an infectious SV40 virus particle and subsequently infected into NIH 3T3 cells (either uninfected or previously infected with Moloney leukemia virus). We found that this hybrid virus, SVLTR1, transforms cells with 10 to 20 times the efficiency of SV40 wild type. Southern blot analysis of these transformed cell genomic DNAs revealed that simple integration of the viral DNA within the retrovirus LTR cannot account for the enhanced transformation of the recombinant virus. A restriction fragment derived from the SVLTR-1 virus which contains an intact LTR was readily identified in a majority of the transformed cell DNAs. These results suggest that the LTR fragment which contains the attachment sites and flanking sequences for the proviral DNA duplex may be insufficient by itself to facilitate correct retrovirus integration and that some other functional element of the LTR is responsible for the increased transformation potential of this virus. We have found that a complete copy of the Harvey murine sarcoma virus LTR linked to well-defined structural genes lacking their own promoters (SV40 early region, thymidine kinase, and G418 resistance) can be effectively used to promote marker gene expression. To determine which element of the LTR served to enhance the biological activity of the recombinant virus described above, we deleted DNA sequences essential for promoter activity within the LTR. SV40 virus stocks reconstructed with this mutated copy of the Harvey murine sarcoma virus LTR still transform mouse cells at an enhanced frequency. We speculate that when the LTR is placed more than 1.5 kilobases from the SV40 early promoter, the cis-acting enhancer element within the LTR can increase the ability of the SV40 promoter to effectively operate when integrated in a murine chromosome. These data are discussed in terms of the apparent cell specificity of viral enhancer elements.